The Effect of Daylight on Visual Comfort: The Case of the Dome as a Classical Architectural Element. - Oussadou, Nesrine (2020)
Visual comfort is a subjective response to the amount and light quality within the workplace at a certain time. The idea behind visual comfort revolves around person’s capability to regulate the light levels surrounding him. Having very small or excessively high amount of light can lead to visual discomfort. This paper investigated and assessed to which extent the use of geometric configurations in the classical architectural elements can fulfill the need for adequate lighting required for acceptable visual comfort. Domes as a classical architectural element function as a main daylight source and at the same time aesthetically pleasing and give the feeling that the room is bigger in size. The dome was chosen as the classical element to be tested in this paper, choosing a building at the University of Sharjah to be the case study. The research used simulation tools including Revit with Insight Plugin and IES with Radiance Plugin Software which will be used to get the glare evaluation and visual comfort index using Daylight Glare Probability metric (DGP), Glare Threshold Differential (GTD), illuminance, Spatial Daylight Autonomy (300/50%) and Annual Sunlight Exposure (1000/250) for different simulated scenarios. The scenarios included cases where the dome was modified and its geometrical configuration were changed in order to enhance the dome capabilities, which included changes in dome’s diameter, drum’s height, and glazing area to drum area percentage. Results showed that, comparing modification done in each variable, highest effect is the glazing percentage =100%, followed by glazing percentage=25%, then drum height =4m, glazing percentage=15% and drum height=3m are almost the same, followed by diameter of 18m and last diameter of 14m. If the dome is already constructed and needed enhancement its preferable to increase the amount of glazing within the dome since it makes the highest impact compared to other variables, with taking into consideration the values of sDA and ASE by testing them in simulations since increasing the glazing percentage increases the possibility of glare to occur. If the architect/designer wants better, uniform and equal daylight distribution bigger diameter can provide it although it doesn’t increase the illuminance levels that much, but if he is looking for higher illuminance level and ensure the glare won’t occur the designer should go with higher height. Equations were concluded showing the relationship of the glazing area with sDA and ASE values. Suggested recommendations for preferred combination of height, diameter and glazing percentage for dome's design and indicated the best orientation per date and time in order to prevent disturbing/intolerable glare.